Sensitivity analysis of a FAO penman monteith for potential evapotranspiration to climate change - Ahmad, Nor Farah Atiqah; Askari, Muhamad; Harun, Sobri; Fadhil, Abu Bakar; Demun, Amat Sairin (UTM Press., 2017)
Sensitivity of the FAO Penman-Monteith (FPM) potential evapotranspiration (PET) model under tropical climates has been studied in the present study. A total of 17 meteorological stations covering Peninsular Malaysia starting from 1987-2003 were used as model inputs. A sensitivity analysis (SA) was carried out using the graphical method for temperature, wind speed and solar radiation within the possible range of ±20% with increments of 5%. From the comparison done on the sensitivity of PET to climatic change, the Kuala Krai station gave the highest percentage change in terms of temperature (±6%). The highest percentage change for wind speed (±2%) and solar radiation (±17%) were shown at the Alor Setar and Kuala Krai stations, respectively. The Alor Setar station had the lowest percentage change for temperature (±0.3%) and solar radiation (±9.9). The lowest percentage change of wind speed (± 0.2%) was observed at the Kuala Krai station. PET percentage changes have a positive correlation to the percentage change of all climatic variables except for the Cameron Highlands station. Results revealed that solar radiation has the most significant effect on PET (±14%), followed by temperature (±4%) and wind speed (±1%). Taken together, these results suggest that solar radiation plays an important role in estimating PET in Peninsular Malaysia.